Community-Acquired Respiratory Paramyxovirus Infection After Allogeneic Hematopoietic Cell Transplantation: A Single-Center Experience. (12th April 2018) - Spahr, Yasmin; Tschudin-Sutter, Sarah; Baettig, Veronika; Compagno, Francesca; Tamm, Michael; Halter, Jörg; Gerull, Sabine; Passweg, Jakob; Hirsch, Hans H; Khanna, Nina
Abstract: Background: Paramyxoviruses include respiratory syncytial virus (RSV), parainfluenza virus (PIV), and human metapneumovirus (MPV), which may cause significant respiratory tract infectious disease (RTID) and mortality after allogeneic hematopoietic cell transplantation (HCT). However, clinical data regarding frequency and outcome are scarce. Methods: We identified all paramyxovirus RTIDs in allogeneic HCT recipients diagnosed by multiplex polymerase chain reaction between 2010 and 2014. Baseline characteristics of patients, treatment, and outcome of each episode were analyzed; ie, moderate, severe, and very severe immunodeficiency (verySID) according to HCT ≤6 months, T- or B-cell depletion ≤3 months, graft-versus-host disease, neutropenia, lymphopenia, or hypo-gammaglobulinemia. Results: One hundred three RTID episodes in 66 patients were identified (PIV 47% [48 of 103], RSV 32% [33 of 103], MPV 21% [22 of 103]). Episodes occurred in 85% (87 of 103) at >100 days post-HCT. Lower RTID accounted for 36% (37 of 103). Thirty-nine percent (40 of 103) of RTID episodes required hospitalization and more frequently affected patients with lower RTID. Six percent progressed from upper to lower RTID. Overall mortality was 6% and did not differ between paramyxoviruses. Sixty-one percent (63 of 103) of episodes occurred in patients with SID, and 20.2% (19 of 63) of episodes occurred in patients with verySID. Oral ribavirin plus intravenous immunoglobulin was administered in 38% (39 of 103) of RTIDs, preferably for RSV or MPV ( P ≤ .001) and for SID patients ( P = .001). Patients with verySID frequently progressed to lower RTID ( P = .075), required intensive care unit transfer, and showed higher mortality. Conclusion: Paramyxovirus RTID remains a major concern in allogeneic HCT patients fulfilling SID and verySID, emphasizing that efficacious and safe antiviral treatments are urgently needed.